2012
DOI: 10.1111/jph.12027
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Two Fungal Isolates from Cotton and Evaluation of their Potential for Biocontrol of Verticillium Wilt of Cotton

Abstract: Two isolates (CVd‐WHw and CVn‐WHg) recovered from Verticillium‐wilt‐symptomatic cotton grown in Hubei Province of China were identified based on their morphology, growth characteristics in culture, specific amplification and identification of internal transcribed spacer (ITS) rDNA sequence. According to the morphological characteristics, specific PCR amplification and ITS sequences, CVd‐WHw was identified as V. dahliae and CVn‐WHg as Gibellulopsis nigrescens. In bioassays, the two isolates had significantly lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 34 publications
3
44
1
Order By: Relevance
“…Gibellulopsis nigrescens (Synonymy: Verticillium nigrescens) as a highly controversial Verticillium spp., is pathogenic on many crops (such like potato, tomato, antirrhinum, eggplant, soybeans and M. sativa [34][35][36][37][38]. However, the recent report revealed that G. nigrescens was a promising biocontrol agent for Verticillium wilt of cotton [39].…”
Section: Discussionmentioning
confidence: 98%
“…Gibellulopsis nigrescens (Synonymy: Verticillium nigrescens) as a highly controversial Verticillium spp., is pathogenic on many crops (such like potato, tomato, antirrhinum, eggplant, soybeans and M. sativa [34][35][36][37][38]. However, the recent report revealed that G. nigrescens was a promising biocontrol agent for Verticillium wilt of cotton [39].…”
Section: Discussionmentioning
confidence: 98%
“…Each strain was inoculated onto 8–10 cotton seedlings at the first euphylla stage by immersing the seedling roots in the conidial suspension. This experiment was replicated three times [38]. The inoculated cotton seedlings were cultivated in a standard greenhouse at 25–30°C under a 16-h/8-h light–dark photoperiod.…”
Section: Methodsmentioning
confidence: 99%
“…Disease progress was recorded from 7 to 24 dpi. The disease index (DI) was calculated based on a five-scale categorization of Verticillium wilt disease on cotton seedlings [38]. …”
Section: Methodsmentioning
confidence: 99%
“…Symptom development was observed from 7 to 26 days after inoculation. Disease severity was rated according to a disease index (DI) based on five-scale categorization of Verticillium wilt disease on cotton seedlings (Zhu et al 2013). The infection assay was repeated three times for each mutant.…”
Section: Pathogenicity Assaysmentioning
confidence: 99%
“…The inoculation concentration was uniformly adjusted to 1 × 10 7 CFU/mL. The infection assay procedure is detailed in our previous report (Zhu et al 2013). Symptom development was observed from 7 to 26 days after inoculation.…”
Section: Pathogenicity Assaysmentioning
confidence: 99%